Population growth and Rural Development in the interface of Climate Change in Nepal: A review - Acharya, Umesh (Pragya Darshan प्रज्ञा दर्शन, 2023)
The objective of this paper is to analyze the relationship between population change and rural development in connection with climate change in Nepal. Climate change has two directional relationship with climate change. Firstly, population growth and rural development act as anthropogenic factors for climate change. On the other hand, climate change and extremities impact population pyramid and damages the rural infrastructures. It is based on secondary data and published and unpublished literatures. The study reveals that there is a strong relationship between climate change, population change and rural development. Many rural people are migrated into the urban areas and young people are trying to shift in abroad for employment where climatic factors are increasingly push factors. Lack of skill oriented education entrepreneurship programs, agricultural extension program people are suffering from different problems. Self help program is needed into the rural areas. So government should rethink to implement the rural development program in Nepal. Poverty become the main sensitive issue of rural areas. Though the government has given emphasis on the rural development of Nepal, so the policy makers should do the research about the successful rural development program in Nepal.